Adsorption study on the removal of cu ions from aqueous solution using NAOH-modified Carica papaya peels - Shuhaimen, Muhammad Shahrain; Abdulah, Erna Normaya; Mohd Salim, Rosliza; Ahmad, Mohammad Norazmi (2017)
Recently, environment contamination by heavy metals has gained much attention due to the significant impact on public health. These heavy metals such as copper (Cu) are non-biodegradable pollutants and they are very difficult to eliminate naturally from the environment. Therefore, this study was conducted to deal with the removal copper (Cu) from an aqueous solution using a highly efficient, environmentally friendly adsorbent from Carica papaya Peels (CPP) prepared by NaOH- treatment modification. The effects of adsorbent mass, pH, initial metal ion solution concentrations and contact time were studied in batch experiments. The optimum adsorbent mass, pH, and contact time for Cu removal are 0.9 g, pH = 3, and 45 min, respectively. SEM and FT-IR were employed to validate the efficiencies of the adsorbents towards lead and copper. As a conclusion, the chemical- treated CPP can be utilized as a potential biosorbent for Cu removal from aqueous solutions.